Iatrogenic Bile Duct Injury Following Cholecystectomy, Surgical Management and Outcome: A Single Center Experience - Faraidon Faiq Ahmed; Tayeb Sabir Kareem; Karzan Seerwan Abdulla; Qalandar Hussein Karim (Advanced Medical Journal)
Background and objectives: Iatrogenic bile duct injury (IBDI) is a serious complication during cholecystectomy caused by a surgeon in apparently healthy patients and is associated with a significant rate of morbidity and a low rate of mortality. Our aim was to review the surgical repair of IBDI and post-operative outcomes regarding morbidity and mortality.